Pengaruh Rotasi KAP, Tenure Audit dan Ukuran Perusahaan Terhadap Kualitas Audit Pada Perusahaan Manufaktur - Eka Putri Yasmin (Journal of Culture Accounting and Auditing, 2023)
The research has a purpose to examine how audit quality is affected by KAP rotation, audit tenure, and firm size. Logistic regression analysis was used to process the data and purposive sampling technique was used to process the sample selection. With this technique, 166 manufacturing companies on the IDX in 2019-2021 have met the criteria in this study. The hypothesis was tested, and the results show that KAP rotation and audit tenure have no effect on audit quality. Nevertheless audit quality can be influenced by the company's size.